UPAYA PENINGKATAN PELAYANAN PADA KANTOR UPTD SAMSAT TULANG BAWANG MELALUI SURVEI TINGKAT KEPUASAN PAJAK KENDARAAN - Suhartina Suhartina; Agus Heri Thama Linto (e-JKPP, 2022)
The problems in this study are: (1) How to improve service quality at the Regional Technical Service Unit One-stop Unit Tulang Bawang Office through a Survey of Motor Vehicle Taxpayer Satisfaction Levels. (2) What are the aspects that hinder the Efforts to Improve Service Quality at the Regional Technical Service Unit One-stop Unit Tulang Bawang Office through the Motor Vehicle Taxpayer Satisfaction Level Survey.The research method used is qualitative research with descriptive analysis method. The use of this method is to examine and describe qualitatively, how the Efforts to Improve Service Quality at the Regional Technical Service Unit Office of One-stop Unit Tulang Bawang through the Motor Vehicle Taxpayer Satisfaction Survey. All data were obtained directly from informants in the field using interview and observation techniques, according to the research objectives to be achieved. Efforts to improve the quality of service at the Regional Technical Service Unit  of the Tulang Bawang One-Stop Administration One-stop Unit, through the Motor Vehicle Taxpayer Satisfaction Survey, have been carried out through the dimensions, namely, (1) Tangibles (Physical Evidence), In generally employees are always present at the office on time and provide friendly service, (2) Empathy (Empathy), In general employees have provided good service to taxpayers, (3) Reliability, Employees who are placed in the service section are employees who have attended training on services, (4) Responsive (Responsive), Employees always try to improve the quality of service to taxpayers, (5) Assurance (Guarantee), employees who work in the service department, have implemented rules in providing services, so there is no differences in service delivery.